2013
DOI: 10.1159/000356947
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Calvarial Defects with <b><i>Escherichia coli</i></b>-Derived rhBMP-2 Adsorbed in PLGA Membrane

Abstract: Objective:Escherichia coli-derived recombinant human bone morphogenetic protein-2 (E-BMP-2) has been shown to be as effective as mammalian cell-derived BMP-2. However, several in vitro and in vivo experiments are still necessary to validate the effectiveness of E-BMP-2 due to the difference in synthesis process, mainly related to protein nonglycosylation. The objective of this study was to investigate whether biodegradable polylactide-co-glycolide (PLGA) membrane is a suitable carrier for E-BMP-2 delivery for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Despite a 110 mg/L production rate of E. coli -derived rhBMP2, its activity and efficacy after refolding is controversial (Bessho et al, 2000 ; Bessa et al, 2008 ; Yano et al, 2009 ; Lee et al, 2010 ). Recently, same preclinical studies showed promising results in using E. coli -produced rhBMP2 for the regeneration of experimentally induced bone defects (Harada et al, 2012 ; Ono et al, 2013 ; Chung et al, 2015 ; You et al, 2016 ), even if the most effective dose as well as the optimal carrier are still to be determined. A comparison between CHO- and E. coli -derived rhBMP2 using a dog critical-size supraalveolar peri-implant model showed that the two rhBMP2s are equally effective in inducing bone formation (Lee et al, 2013 ); however, no economic analysis was provided in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a 110 mg/L production rate of E. coli -derived rhBMP2, its activity and efficacy after refolding is controversial (Bessho et al, 2000 ; Bessa et al, 2008 ; Yano et al, 2009 ; Lee et al, 2010 ). Recently, same preclinical studies showed promising results in using E. coli -produced rhBMP2 for the regeneration of experimentally induced bone defects (Harada et al, 2012 ; Ono et al, 2013 ; Chung et al, 2015 ; You et al, 2016 ), even if the most effective dose as well as the optimal carrier are still to be determined. A comparison between CHO- and E. coli -derived rhBMP2 using a dog critical-size supraalveolar peri-implant model showed that the two rhBMP2s are equally effective in inducing bone formation (Lee et al, 2013 ); however, no economic analysis was provided in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, our research group recently succeeded in producing BMP-2 using an Escherichia coli production system (E-BMP-2), which is particularly attractive for biotechnology because of the ability of E. coli to grow rapidly and at a high density on inexpensive substrates [Kubler et al, 1998;Yano et al, 2009]. Previously, our group demonstrated the osteoinductive capacity of E-BMP-2 in vitro and ectopic and orthotopic bone formation in vivo [Yano et al, 2009;Ono et al, 2013]. In the dental field, several reports have shown that E-BMP-2-coated implants enhance bone-to-implant contact (BIC) [Lee et al, 2013] and bone regeneration in bone closure of a sinus window .…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, it was shown that in situ gelling hydrogel composite with a concentration of 50 ug/mL BMP-2 (2 µg per implant in a 5 mm defect) successfully regenerated bone. In other preclinical studies with BMP-2 carriers, the BMP-2 dose needed to heal a critical sized defect is generally higher; in a rat calvarial model similar to the one used in the current study, complete healing of the defects is achieved with poly lactic-co-glycolic acid (PLGA) membranes adsorbed with 5 mg/mL of BMP-2 (Ono et al, 2013). Young et al (2009), using a 8 mm rat calvarial model and 0.5 µg and 1 µg of BMP-2 per implant delivered with gelatin particles, show an incomplete bone bridging.…”
Section: Discussionmentioning
confidence: 96%